Direct to consumer advertising in pharmaceutical markets - Kurt R. Brekke; Michael Kuhn (Center for Economic Studies and ifo Institute (CESifo), 2005)
We study effects of direct-to-consumer advertising (DTCA) in the prescription drug market. There are two pharmaceutical firms providing horizontally differentiated (branded) drugs. Patients differ in their susceptibility to the drugs. If DTCA is allowed, this can be employed to induce (additional) patient visits. Physicians perfectly observe the patients' type (of illness), but rely on information to prescribe the correct drug. Drug information is conveyed by marketing (detailing), creating a captive and a selective segment of physicians. First, we show that detailing, DTCA and price (if not regulated) are complementary strategies for the firms. Thus, allowing DTCA induces more detailing and higher prices. Second, firms benefit from DTCA if detailing competition is not too fierce, which is true if investing in detailing is sufficiently costly. Otherwise, firms are better off with a ban on DTCA. Finally, DTCA tends to lower welfare if insurance is generous (low copayments) and/or price regulation is lenient. The desirability of DTCA also depends on whether or not the regulator is concerned with firms' profit.
Keywords: I11; M37; L65; L13; 330; marketing; pharmaceuticals; oligopoly; Werbung; Pharmazeutisches Produkt; Oligopol